Design and performance analysis of the miniaturised water‐filled double‐ridged horn antenna for active microwave imaging applications. Issue 11 (1st August 2015) - Latif, Saeed Iftakhar; Flores‐Tapia, Daniel; Pistorius, Stephen; Shafai, Lotfollah
Abstract : The design and analysis of a miniaturised double‐ridged horn antenna for active microwave imaging application are presented in this study. For such an application, a physically small horn is required. For effective signal penetration, a low frequency of operation (about 1.4 GHz) is selected. An array of these sensors is intended for use in a cylindrical breast imaging system, which is under development in the authors laboratory. The miniaturisation is achieved by loading the double‐ridged horn antenna with distilled water ( ε r = 76), a high permittivity, but easily available material. Further size reduction is achieved by reducing the aperture size and flare length in the horn section. The frequency response and both near‐ and far‐field patterns were studied. Two simplified prototypes were fabricated, and as per the system requirements, tested in a cylindrical container filled with distilled water. Measured and simulated reflection and transmission responses are discussed. Measured radiation patterns are compared with the simulated ones to validate the analysis.